Skeptisisme Personal Dan Situasional Terhadap Keputusan Audit: Sebuah Studi Eksperimen - Rudy Suryanto; Azkia Fiki Sani; Hafiez Sofyani (Jurnal Akuntansi, 2018)
The study aims to examine the influence of personal and situational scepticism on audit judgement. Situational scepticism can be presented by audit experience from previous years (Client-Specific Experience). The study uses an experiment 2x3 factorial design between subjects with divides personal scepticism into high and low, and case of situational scepticism about audit experience from previous years into positive, neutral and negative. The subject of experiment are 84 undergraduate accounting department students who have learned the course of auditing. ANOVA is applied as a tool to attempt the hypotheses. The result reveals that audit judgement made by auditor is influenced by their experience with client from previous years.